Marketing Requirements for Public Services of an Administrative Nature - Soufi, Nabil; Bourihane, Farouk (Finance and Business Economies Review, 2022)
Marketing public services considered as one of modern topics worthy of research, we point out here that despite difference in the opinions of researchers between supporters of this proposition and conservatives, most trends and surveys indicate existence of positive attitudes regarding need for public administrations to market their services (of an Administrative Nature) in order to improve their image and restore a confidence of their customers. Previous goal may be achieved despite the difficulties that may face the process due to the peculiarities of public administrations., unlike business organizations and public organizations of a commercial or economic nature, and here this study came to examine the subject by adjusting most important requirements, especially those related to re-adapting concept of marketing to conform to those peculiarities, By shifting from (4Ps) to (4Cs) approach.